2011
DOI: 10.1108/13673271111179271
|View full text |Cite
|
Sign up to set email alerts
|

Organizational factors to support knowledge management and innovation

Abstract: Purpose -The purpose of this paper is to analyze how organizational factors such as cultural values, leadership and human resource (HR) practices influence knowledge exploration and exploitation practices and innovation via an empirical study.Design/methodology/approach -From the knowledge-based view of the firm, six hypotheses were established and statistically tested in a sample of 111 Spanish companies belonging to innovative industries. Survey methodology was used with the aim of gathering data regarding k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
231
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(273 citation statements)
references
References 87 publications
12
231
0
13
Order By: Relevance
“…At the same time, the correct use of such systems may support organizational performance since LOCs can generate dynamic tension between opportunistic innovation and predictable goal achievement (Simons 1995). All in all, a MCS must provide objectives and incentives, and support the development of an organizational culture that fosters knowledge transfer (Donate and Guadamillas 2011).…”
Section: Management Control Systemmentioning
confidence: 99%
“…At the same time, the correct use of such systems may support organizational performance since LOCs can generate dynamic tension between opportunistic innovation and predictable goal achievement (Simons 1995). All in all, a MCS must provide objectives and incentives, and support the development of an organizational culture that fosters knowledge transfer (Donate and Guadamillas 2011).…”
Section: Management Control Systemmentioning
confidence: 99%
“…Thomas (2006) suggested that organizations needed a small number of the following factors: top management leadership, human resources policy, compensation schemes, collaboration, and measurement. Other studies have identified these factors as culture, technology, leadership, human resources practices, and innovation (Donate & Guadamillas, 2011;Yusuf & Wanjau, 2014). Holsapple and Joshi (2000) carried out a literature review that yielded eight factors that potentially influenced knowledge management in organizations.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…Thomas found these factors to consist of management support, human resources policy, collaboration, and reward system. Donate and Guadamillas (2011) provided empirical evidence on the relationship between knowledge management and organizational elements such as culture, leadership, human resources practices, and innovation. Other factors that have been found to correlate positively with knowledge management activities include leadership (Singh, 2008), communication flows (Rosmaini &Woods, 2007), and collaboration and training (Schulte &Wang, 2004).…”
Section: Organizational Factors and Knowledge Management Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Donate and Guadamillas (2011), in an empirical study of 111 Spanish firms, find that organizational culture, leadership and Human Resource practices affect KM practices on innovation outcomes. In his theoretical piece, Rai (2011) claims that organizational culture is critical in building and reinforcing new knowledge but admits that little is known about how this works.…”
Section: Knowledge Management and Culturementioning
confidence: 99%